The Influence of Carbon Emission Disclosure and Green Innovation on Firm Value with Profitability as a Moderating Variable - Nabila, Tasya; Wardhani, Nurhastuty Kesumo (Golden Ratio of Auditing Research, 2026)
This study aims to analyze the effects of Carbon Emission Disclosure and Green Innovation on firm value, with Profitability as a moderating variable. Firm value in this study is measured using the Tobin Q ratio. The data were obtained from Annual Reports and Sustainability Reports through purposive sampling, resulting in a sample of 19 companies with a total of 76 observations. Data analysis was conducted using Moderated Regression Analysis (MRA) in SPSS Software version 26 to examine the effect of independent variables and the role of the moderating variable. The hypothesis testing results indicate that Carbon Emission Disclosure and Green Innovation have a significant effect on firm value, whereas Profitability does not moderate the effect of Carbon Emission Disclosure and Green Innovation on firm value. These findings suggest that when companies transparently disclose their carbon emission data and undertake environmentally supportive innovations, it enhances the firm's value. Meanwhile, the level of profitability does not alter or influence the relationship between carbon emission disclosure and green innovation with firm value.